2012
DOI: 10.1159/000345168
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Maternal UPD6 with Prenatal Growth Restriction

Abstract: We report a child with segmental maternal uniparental isodisomy of chromosome 6, involving most of the long arm distal to 6q16, detected by SNP microarray. Clinical features include prenatal growth restriction, global developmental delay, and severe gastro-esophageal reflux disease. Maternal uniparental disomy (UPD) of chromosome 6 has previously been reported to cause intrauterine growth restriction. Paternal UPD of this chromosome is well known to cause transient neonatal diabetes mellitus. We discuss report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Among all 17 upd(6)mat patients, five were homozygous for recessive mutations, and exhibited the respective phenotype (e.g., 3M syndrome, AGS; Table 1). In 2013, Poke and colleagues (Poke et al 2013) suggested that homozygosity of an autosomal recessive mutation in 6q16.1qter might cause some clinical features of the condition, or at least for IUGR. However, the comparison of the available SNP data in upd(6)mat patients (n = 6) reveals that there is no overlap of isodisomic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Among all 17 upd(6)mat patients, five were homozygous for recessive mutations, and exhibited the respective phenotype (e.g., 3M syndrome, AGS; Table 1). In 2013, Poke and colleagues (Poke et al 2013) suggested that homozygosity of an autosomal recessive mutation in 6q16.1qter might cause some clinical features of the condition, or at least for IUGR. However, the comparison of the available SNP data in upd(6)mat patients (n = 6) reveals that there is no overlap of isodisomic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The one case of isodisomy upd(6)mat which did not have IUGR had segmental isodisomy UPD with affected regions on the p and q arms [Gumus et al, ]. Poke et al [] noted a common region at 6q16.1qter that, when subjected to paternal UPD, resulted in IUGR. This suggested an importance of heterozygosity of this region for fetal growth, or the possible presence of an important autosomal recessive gene for growth in this region [Poke et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Poke et al [] noted a common region at 6q16.1qter that, when subjected to paternal UPD, resulted in IUGR. This suggested an importance of heterozygosity of this region for fetal growth, or the possible presence of an important autosomal recessive gene for growth in this region [Poke et al, ]. Imprinted candidate genes on chromosome 6 influencing growth have been suggested, including overexpression of maternally imprinted PLAGL1 and HYMAI genes at 6q24.2 and gain of methylation of IGFR2 (6q25.3), which may function to decrease circulating growth factor levels [Salahshourifar et al, ; Poke et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations